2017
DOI: 10.1080/18626033.2017.1425320
|View full text |Cite
|
Sign up to set email alerts
|

Developing green infrastructure design guidelines for urban climate adaptation

Abstract: Existing scientific literature Evidencebased UGI design practice Revised design guidelines for climateresponsive UGI Preliminary design guidelines for climateresponsive UGI Questionnaire Criteria Methods Assessment of preliminary design guidelines in design studios Observations Plan analyses Usefulness Appreciation Comprehensibility Applicability Feasibility

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…Second, some landscape architects are not very familiar with microclimate, so that they consider it less at the concept exploration phase [43][44][45][46][47]. Including microclimate modification in landscape architecture education can improve student understanding and appreciation of the role of microclimate in design.…”
Section: Suggested Areas Of Future Researchmentioning
confidence: 99%
“…Second, some landscape architects are not very familiar with microclimate, so that they consider it less at the concept exploration phase [43][44][45][46][47]. Including microclimate modification in landscape architecture education can improve student understanding and appreciation of the role of microclimate in design.…”
Section: Suggested Areas Of Future Researchmentioning
confidence: 99%
“…Besides addressing the objective and subjective reality and being spatially explicit, scientific microclimate knowledge needs to be useful for design practitioners in order to warrant its implementation in urban design practice. Usefulness of knowledge, and in particular, of design guidelines, in this thesis was conceptualised as the composition of comprehensibility for designers, applicability in design processes, and feasibility in design practice (Klemm et al, 2017a). This consistent set of criteria was developed from earlier studies that indicated obstacles between scientific microclimate evidence and the needs of design practitioners (e.g., Brown and Corry, 2011, De Schiller and Evans, 1990, Eliasson, 2000, Lenzholzer, 2010a, Norton et al, 2015, Pijpers-van Esch, 2015.…”
Section: The Usefulness Of Scientific Evidencementioning
confidence: 99%
“…Also in the context of urban climate adaptation, this integration is an important contribution that environmental designers can make. Against the backdrop of heat stress as a result of increasing temperatures and enhanced urban heat islands, climate-responsive design is concerned with creating urban environments that are thermally comfortable (Brown et al, 2015;Klemm et al, 2017). These designs consider the microclimate effects of, amongst others, the orientation of streets and buildings, type of surface materials, and types and locations of vegetation, whilst also accounting for aspects such as functionality, aesthetic appeal and maintenance (Jacobs et al, 2020;Klemm et al, 2017;Lenzholzer and Brown, 2013).…”
Section: Resource-conscious Urban Planning and Designmentioning
confidence: 99%
“…Future research should explore how descriptive and analytical insights from UM assessments can be translated in such a way that they enable judgment what action to take in which circumstances (Campbell, 2012). A promising approach could be to formulate UM planning and design guidelines: "evidence-based, universally applicable knowledge that guides urban design actions in a variety of site-specific spatial and functional circumstances, and that is considered useful by design practitioners" (Klemm et al, 2017) (see 6.4.1).…”
Section: Towards Comprehensible and Applicable Evidence For Practicementioning
confidence: 99%
See 1 more Smart Citation